(untitled) (AIUB Journal of Science and Engineering (AJSE), 2021)
Undergraduate students are considered susceptible in terms of anxiety, drug abuse, depression, and bad dietary habits in comparison to the general people. Their academic and psychological facets have severely been altered due to COVID-19 pandemic. The objective of this study is to identify the effect of COVID-19 on the academic and psychological aspects of undergraduate students in Bangladesh accompanied by other pertinent factors. Data were accumulated from the undergraduate students of the Fall semester 2020-21 of American International University-Bangladesh (AIUB) by questionnaire provided through Microsoft Forms. The associations among the variables were assessed through the chi-square test. All the statistical analyses required to meet the goals of the study were done through Statistical Package for Social Sciences (SPSS). Nearly one-fourth of the students suffered from anxiety and depression at an extreme level while close to one-third of them suffered quite a bit signaling a tormenting psychological state of the students. Chi-square tests found that depression, anxiety, study hour, assessment of online learning, and income issue due to COVID-19 of the student had a highly significant association with effects on their study and psychological aspects. Failure to address the aforesaid issues during an epidemic might have negative consequences on the academic and psychological aspects in the long run.